Nondifferentiable Multiobjective Programming Problem under Strongly K-Gf-Pseudoinvexity Assumptions - Dubey, Ramu; Mishra, Lakshmi Narayan; Sánchez Ruiz, Luis Manuel; Sarwe, Deepak Umrao (Mathematics (Basel), 2020)
In this paper we consider the introduction of the concept of (strongly) K- G f -pseudoinvex functions which enable to study a pair of nondifferentiable K-G- Mond-Weir type symmetric multiobjective programming model under such assumptions.